Analysis of the Effect of Profitability, Liquidity and Company Size on Debt Policy (Empirical Study on Metal and Other Subsector Companies Listed on The Indonesia Stock Exchange for the 2015-2020 Period) - Budhi Pamungkas Gautama; Eka Surachman; Igga Zhandraverina (The International Journal of Business Review (The Jobs Review), 2022)
This study aims to determine the effect and description of Profitability, Liquidity, Company size and Debt Policy for metal and other sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period. The method used is to describe the variables studied and determine the effect of profitability, liquidity and company size on debt policy. The data used in this study are the ratios of ROA, CR, Size and DER during the 2015-2020 period. The data processing used is panel data regression analysis. The hypothesis testing used is the regression significance test and the regression coefficient significance test. Based on the results of the regression significance test, it is found that the regression model created can be accepted and continued, while from the results of the regression coefficient significance test, it is found that profitability has no significant effect on debt policy while liquidity and company size have a positive effect on debt policy.